2020
DOI: 10.1136/bmjdrc-2019-001078
|View full text |Cite
|
Sign up to set email alerts
|

Serum cell-free DNA and progression of diabetic kidney disease: a prospective study

Abstract: AimsCell-free DNA (cfDNA) is associated with diabetes and cardiovascular diseases. Our study was to evaluate whether serum cfDNA could predict the progression of diabetic kidney disease (DKD).MethodsIn this prospective study, a total of 160 patients with DKD were enrolled, and the kidney function was followed up by measurement of estimated glomerular filtration rate (eGFR) and urinary albumin–creatinine ratio (UACR) for three consecutive years. At baseline, concentrations of serum cfDNA were measured. DKD prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Furthermore, in non-dialyzed patients, urinary levels of cfDNA were predictors of unfavorable renal outcomes [133]. These findings were consistent with the results of Li et al (2020), which demonstrated that increased serum cfDNA levels were associated with an increased risk of diabetic nephropathy in a cohort of diabetic patients [134], suggesting the potential of cfDNA as a biomarker of disease progression.…”
Section: Biomarkers Of Inflammationsupporting
confidence: 88%
“…Furthermore, in non-dialyzed patients, urinary levels of cfDNA were predictors of unfavorable renal outcomes [133]. These findings were consistent with the results of Li et al (2020), which demonstrated that increased serum cfDNA levels were associated with an increased risk of diabetic nephropathy in a cohort of diabetic patients [134], suggesting the potential of cfDNA as a biomarker of disease progression.…”
Section: Biomarkers Of Inflammationsupporting
confidence: 88%
“… 96 , 97 There is currently a paucity of data on dd-cfDNA levels in this setting; however, host-derived circulating DNA has been reported in systemic lupus erythematous, progressive diabetic kidney disease, and urinary mitochondrial DNA has also been described in IgA nephropathy. 98 - 100 It should be noted that cell-free DNA may be extruded during the inflammatory process of neutrophil extracellular traps formation. 101 NETosis involves the deployment of extracellular chromatin, which is speculated to entangle microbes as host-defense mechanism, and is seen in a number of autoimmune conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although ecDNA was higher in hemodialysis patients compared to CKD or peritoneal dialysis patients, no differences were observed in general between patients and healthy participants [ 209 ]. Despite this, it seems that ecDNA may have a broader potential for disease prediction, since the increase of serum levels was associated with the risk of progression of diabetic kidney disease [ 210 ]. Apart from its potential prognostic features, removal of excess ecDNA by DNase was successful in amelioration of IRI-induced AKI [ 211 ].…”
Section: Citrullination Nets and Pads In Chronic Diseasesmentioning
confidence: 99%